The contribution of Socio-Economic factors to adoption of inorganic fertilizers among maize farmers in Western Uganda - Dick Chune Midamba; John Atsu Agbolosoo; Fredrick Ochieng Ouya; Mary Kwesiga (Discover Sustainability)
Abstract Inorganic fertilizers boost soil fertility, resulting in high crop productivity. However, low adoption rates have been reported in many Sub-Sahara African countries. Strikingly, the drivers of adoption of inorganic fertilizers has not been adequately researched on in Uganda. Thus, this research investigated the nexus between inorganic fertilizer adoption and socio-economic predictors using primary data gathered from 200 maize farmers in Western Uganda. The study employed descriptive statistics and Binary logistic model for data analysis. Results revealed that a mere 32% of farmers incorporated inorganic fertilizers in their agricultural practices. Notably, those who adopted inorganic fertilizers demonstrated a yield increase of 55.38 kg per acre compared to non-adopters. Econometric analysis indicated that socio-economic predictors such as farm size, non-agricultural income, farm location, household size, group affiliation, and use of hired labor positively influenced the adoption of inorganic fertilizers. Conversely, factors including gender, distance to markets, and fertilizer costs negatively impacted adoption rates. The study recommends subsidizing inorganic fertilizer prices to enhance accessibility. Agricultural extension services should focus on female farmers and those with smaller land holdings, educating them about the advantages of inorganic fertilizer use. The formation of farmer support groups is strongly encouraged, as it has been shown to promote the adoption of inorganic fertilizers.